Early-Age Strength Measurement of Shotcrete. (10th November 2015) - Mohajerani, Abbas; Rodrigues, Daniel; Ricciuti, Christian; Wilson, Christopher
Abstract : Shotcrete or sprayed concrete is a special concrete designed for spraying onto a surface, as a construction material. With shotcrete application as a ground support system ever-present in both mining and tunnelling sectors, a major requirement of drive progression is to determine when it is safe to reenter beneath freshly sprayed concrete. Accurately determining this time is of paramount importance. Generally, this reentry time is based on measuring the developing strength of shotcrete until an adequate strength value is reached. The issue with current practice is that there is no widely accepted or generally preferred method that accurately assesses the shotcrete lining's true early-age strength. However, there are a number of strength tests that are commercially available and used in the industry; these include the soil penetrometer, needle penetrometer, bolt screws, beam end testers, and drilled core samples. This paper researches into these testing methods and their characteristics in order to determine their accuracy, testing ranges, and suitability for in situ use in the tunnelling and mining industry. The investigation ultimately reveals that current methods all have substantial shortcomings. Based on these findings, recommendations are proposed for the applicable use of the current testing methods and recommendations for future improvements.